THE MEANING OF OPENING TEASER OF THE TALK-SHOW DUA SISI AS PROGRAM IDENTITY - Oktora, Dina Dwika (Seni Media Rekam ISI Surakarta, 2020)
A television program is usually equipped with an opening teaser as the identity of the program. The opening teaser on TVONE's show, entitled